Sensitive Anodic Stripping Voltammetric Determination of Indium(III) Traces Following Double Deposition and Stripping Steps. Issue 4 (28th January 2017) - Gęca, Iwona; Korolczuk, Mieczyslaw
Abstract : A procedure for the determination of In(III) by anodic stripping voltammetry following double deposition and stripping steps was described. Two environmentally friendly electrodes with different surface areas – glassy carbon macroelectrode and an ensemble of carbon composite microelectrodes – modified with bismuth films were used for the measurements. Parameters affected In(III) determination were optimized. Under optimized conditions the calibration graph was linear from 5 × 10 −10 to 2 × 10 −8 mol L −1 following deposition time of 300 s at both working electrodes. The application of double deposition and stripping steps led to a very low detection limit of indium determination of 1.5 × 10 −10 mol L −1 . Possible interferences from contaminant metal ions were studied and the procedure of elimination of Cd(II) effect on In(III) signal was proposed. The analysis of natural water sample was successfully performed with the use of the presented methodology.